Observation of eczema patients with asthenic syndromes using Traditional Chinese Medicine treatment - Leow, Kimberly Xin Ting (2015)
Atopic dermatitis is a common chronic dermatological disease that affects many around the world. Traditional Chinese Medicine (TCM) is gaining popularity amongst many for its effective treatment outcomes for various diseases. The objective of this study is to investigate the use of TCM in the treatment of eczema patients diagnosed with asthenic syndromes, in particular the use of cupping which has not been extensively studied. 13 participants received herbal medicinal treatment, and a selected few also received cupping treatment on the Shenque acupoint for six weeks. The patients were assessed at enrollment (T0), the third (T3) and sixth (T6) week of the study period. The Severity Scoring of Atopic Dermatitis (SCORAD) and Dermatology Life Quality Index (DLQI) were used as the outcome measures. The main results demonstrated 1) an overall drop in the average SCORAD and DLQI scores, when comparing between T0 and T3, but a less significant drop in the mean scores, when comparing between T0 and T6; 2) a greater drop in the average SCORAD and DLQI scores in the MTC group as compared to the MT group. Nonetheless, the results are not conclusive of the efficacy of TCM treatment on atopic dermatitis with asthenic syndrome.